A Geostatistical Approach to Integrating Data from Multiple and Diverse Sources: an Application to the Integration of Well Data, Geological Information, 3D/4D Geophysical and Reservoir‐Dynamics Data in a North‐Sea Reservoir - Caers, Jef; Castro, Scarlet (Subsurface Hydrology: Data Integration for Properties and Processes, 2007)
This chapter contains sections titled: Introduction Subsurface Data and Spatial Modeling Integration of Static and Dynamic Data Conclusions